KEBIJAKAN PENATAAN DAN PENGELOLAAN PASAR BADUNG KOTA DENPASAR MENUJU PASAR TRADISIONAL YANG BERBASIS MODERN - Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2014)
ABSTRACT Â The structuring and management policies Denpasar Badung Market is a research that aims to rearrange Denpasar Badung Traditional Market in Denpasar Mayor of realizing policy guidance traditional market and modern store, this research successfully analyzed the constraints structuring and management of Badung Market, among others, lack of instructions from the center, so that the government under the central government havenâ€™t been able to apply the rules of Denpasar Mayor, Other contributing factors are less assertive market local company in curbing traders, the next of delay lies in the decline in the arrangement of Badung Market funds, of delay budgets derived from the central cause of regional government has not dared to do the arrangement, especially the lack of human resources in implementing policies, constraints cooperation should be mutually coordinated between the PD. Market and Mayor of Denpasar must await the decision of the central in organizing the Badung Market. Keywords: Policy, Planning, Management, Traditional Market, Modern Market.